Elementary School Teacher Education Student’s Perceptions of English Class - Syaefani Arif Romadhon; M Sofyan Firmansyah (Journal of English Language Learning, 2026)
This study aims to explore the perceptions of undergraduate students in the Elementary School Teacher Education program regarding their English courses. The research method used is a quantitative descriptive study employing a survey approach, involving all active students in the even semester of the 2025/2026 academic year as the sample. The research instrument consists of a 5-point Likert scale questionnaire that measures the clarity of teaching methods and instructions, student engagement, the relevance of the material, the variety of methods and media, as well as the impact of learning on motivation, self-confidence, and interest in learning. The results of the study indicate that students have a positive perception of the courses, particularly regarding the relevance of methods, classroom interaction, and the use of engaging media. Active methods such as group discussions, storytelling, game-based learning, and project-based learning are considered more effective than one-way lectures because they enhance student engagement and understanding. However, some students still experience low self-confidence and difficulty retaining material. These findings emphasize the need for communicative, contextual, and practice-oriented learning strategies to improve the English proficiency of prospective elementary school teachers. The research results provide a foundation for the development of more effective and relevant learning strategies.